Factors Contributing To the Reluctance to Participate In Widespread Political Engagement (Iraq as a Case Study) - Al-Mousawi, Amer (Journal of Legal Sciences, 2026)
The research addresses the factors contributing to the reluctance to participate politically in Iraq, through studying the social, cultural, political and economic factors that influence the process of political reluctance, through studying the impact of weak political awareness, societal traditions and conservative values ​​that contribute to marginalizing large segments of society, especially women and youth, which hinders their effective participation. It also reviews political and economic factors such as the absence of effective democracy and administrative and political corruption, which leads to a lack of trust in government institutions. In addition, the research indicates the impact of sectarian and ethnic tensions in Iraq on the political system, and how they contribute to limiting political participation. With proposals and solutions for each reason for reluctance.